Advantages of quadrantectomy in bitches with mammary neoplasm - Caldas, Saulo Andrade; Oliveira, Mariana Correia; Oliveira, Lucinéia Costa; Freire, Kelly Regina Freitas; Campos, Ana C Carolina; Pires, Ana Paula de Castro; Nogueira, Vivian de Assunção; Cid, Gabriela de Carvalho (Brazilian Journal of Veterinary Medicine, 2018)
A great number of surgical procedures have been proposed for the treatment of mammary tumors in bitches; however, few surveys have compared the accuracy of different techniques in dogs. Our study aimed to establish a quadrantectomy clinical and surgical protocol for the treatment of mammary tumors in bitches, similar to those performed in women. Between March 2014 and December 2015, 154 bitches were admitted to the Obstetric Sector of the Veterinarian Hospital of the Rural Federal University of Rio de Janeiro. One hundred and forty-one of those bitches presented different variants of mammary tumors and were treated with surgical procedures. Pre-operational evaluation included tumor staging through the TNM system and assessment of surgical risk. The following agents were used throughout the surgical procedures: Acepromazine 0.2% (0.2 mg/kg, IM) or Diazepam for pre-anaesthesia, a Diisopropylphenol 0.5% (2.0 to 8.0 mg/kg, IV), IM during the general anaesthesia induction, and closed-circuit Isoflurane in the stage of management of anaesthesia. Quadrantectomy was performed as a maneuver to prevent tumor recurrence. The maneuver proved effective due to the 95.5% survival rate, compared to the 90.5% survival rate of right or left unilateral mastectomy and bilateral mastectomy techniques. Quadrantectomy in association with dissection method, surgical drain, and compression bandaging was considered an effective and easily applicable surgical procedure in bitches with mammary tumors